2014
DOI: 10.1007/s11368-014-0973-6
|View full text |Cite
|
Sign up to set email alerts
|

Are urban soils similar to natural soils of river valleys?

Abstract: Purpose Urban soils and soils of river valleys are constituted of heterogeneous materials that have been manipulated, disturbed or transported at different spatial and temporal scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The urban soil material was collected from a Terric Anthrosol (Siltic) (IUSS Working Group, 2007)/ANTHROPOSOL RECONSTITUÉ carbonaté, nivelé, polyphasé à matériau terreux et à arte-facts (Baize and Girard, 2009) in a stone quarry restored in 1995 (Switzerland, canton of Neuchâtel, 47°0′20″ N, 6°54′46″E). The alluvial and urban soil profiles were both constituted on a sequence of three soil horizons, respectively Aca/ JpcaMca/IIDcaMca and LtpAzca/IILtpAzcaSzca/IIIDca (Baize and Girard, 2009) as described by Amossé et al (2014).…”
Section: Soil Properties and Earthworm Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The urban soil material was collected from a Terric Anthrosol (Siltic) (IUSS Working Group, 2007)/ANTHROPOSOL RECONSTITUÉ carbonaté, nivelé, polyphasé à matériau terreux et à arte-facts (Baize and Girard, 2009) in a stone quarry restored in 1995 (Switzerland, canton of Neuchâtel, 47°0′20″ N, 6°54′46″E). The alluvial and urban soil profiles were both constituted on a sequence of three soil horizons, respectively Aca/ JpcaMca/IIDcaMca and LtpAzca/IILtpAzcaSzca/IIIDca (Baize and Girard, 2009) as described by Amossé et al (2014).…”
Section: Soil Properties and Earthworm Samplingmentioning
confidence: 99%
“…Comparison of urban soils with natural ones is useful in order to assess if soil fauna has similar effects on soil processes in the urban context as in natural setting. Alluvial soils seem to be a good reference for urban soils in that they are both young soil systems which are constituted of mate-rials that have been manipulated, disturbed or transported at different spatial and temporal scales (Amossé et al, 2014). In this context, the aim of this study was to compare the effects of two endogeic earthworm species, Allolobophora chlorotica (pink morph, Savigny, 1826) and Aporrectodea rosea (Savigny, 1825), on the SOM dynamics and the soil structure in urban and alluvial soil materials.…”
Section: Introductionmentioning
confidence: 99%
“…This study introduced the contents of heavy metals, organic carbon, pH, contents of nutritive elements (N, P, K), and tree biomass production [60] in cluster diagrams. Another study used this method to detect the similarities between urban soil and natural soil from a river valley based on physical properties (coarse, clay, silt, and sand contents) and chemical properties (pH, organic carbon, total nitrogen and phosphorus, CEC, content of carbonates, and C/N ratio) [61]. To assess the pollution of heavy metals in a very industrialized and urbanized area in China, the authors used cluster analyses and observed five big clusters, taking into account the contents of 11 heavy metals [26].…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 1, this data re‐aggregation step (i.e., the soil classification from the 3–4D property model), as indicated by the blue double‐headed arrow, may be carried out at shorter and longer time intervals to account for effects of the mass changes due to faster and slower geo‐bio‐hydro‐mechanic processes involved. Usually, significant changes in the horizon thickness and features are expected to be slow except for soil erosion and anthropogenic processes (e.g., Amossé et al., 2015). In this way, the sensitivity of the classification with respect to characteristic soil properties and the temporal stability of soil map information could be analyzed.…”
Section: Mechanistic Modelingmentioning
confidence: 99%